A Critique on “The Study of Making Method and Golbandiin Gereh Panj Inlay” - Samira Arab; Seyed Abdolmajid Sharifzadeh (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Inlay is one of the traditional arts related to wood with a variety of designs, which is not very popular today. The construction of Inlay, especially the Gereh Inlay, has been important since the Safavid period, and this method has been used in the construction of Inlay until the contemporary period. It is important to pay close attention to the research and critique its published sources in the field of research Which will bring about achievements such as introduction, presentation, and pathology. The deficiency of specialized information among the few published articles is Tangible and visible. The article on “The Study of Making Method and Golbandi Gereh Panj Inlay” has been published in the Scientific Research Quartely Negareh Journal by Maryam Akbarzadeh and Mohammad Sadegh Mirza Abolghasemi in Autumn1397, No.47and pages 82-95 with the intention of examining Gereh Panj Inlay. The necessity to critique and evaluate this article indicates the importance of Gereh Inlay and emphasizes the publication of specialized and accurate information about Gereh Inlay. Gereh Inlay, with a rich background, is less important today for a number of reasons, including the difficulty of preparing the raw materials for the manufacturing process. Therefore, addressing the end of the Gereh and documenting it have been among the importance of research topics. This study tries to criticize this article, which has been done in content and scientific form, it also tries to explain the shortcomings, though few, in the specialized stages of making Gereh Panj Inlay.